تاثير الاستحواذ و التوسع على الأداء المالي للمؤسسة دراسة حالة استحواذ شركة أرامكو السعودية على شركة سباك للفترة الممتدة من (2017 الى 2023) - يوسف معيوه; قدور قادي; ايمن غندير (جامعة الوادي University Of Eloued, 2025)
"تهدف هذه الدراسة إلى إبراز أثر عمليات الاستحواذ والتوسع على الأداء المالي للشركة، وذلك من خلال دراسة حالة استحواذ شركة أرامكو السعودية على شركة سابك عام 2020 وذلك باستخدام النسب المالية الخاصة بمؤشرات السيولة، النشاط والربحية، حيث تم تقسيم فترة الدراسة الى قسمين، مرحلة قبل الاستحواذ من سنة 2017 الى سنة 2019 ومرحلة بعد الاستحواذ من سنة 2021 الى سنة 2023، كما جمعت بيانات الدراسة بشكل أساسي من القوائم المالية. تم استخدام المنهج الوصفي التحليلي لعرض الإطار النظري وتحليل المؤشرات المالية الى جانب منهج دراسة الحالة باعتباره الأنسب لتحليل تجربة الاستحواذ. أظهرت نتائج الدراسة أن هناك أثر للاستحواذ على الأداء المالي بحيث لاحظنا ان هناك تحسنا في نسب السيولة، وأظهرت النتائج ارتفاع ملحوظ بعد الاستحواذ، وتأثير محدود أو غير مباشر على نسب النشاط، بينما هناك انخفاض في نسب الربحية. " This study aims to explore the impact of acquisition and expansion operations on the financial performance of the company , this is done through an analytical study of the acquisition of the Saudi Aramco company over the Saudi SABIC company in 2020 using financial ratios related to liquidity activity profitability and leverage the study was conducted in two stages the pre-acquisition stage from 2017 to 2019 and the post-acquisition stage from 2021 to 2023 the data for the study was collected primarily from the financial statements. ""The descriptive-analytical method was employed to present the theoretical framework and analyze the financial indicators, in addition to the case study method, which is considered the most appropriate for analyzing the acquisition experience."" The study results showed that the acquisition had an ampact on financial performance,as there was a positive effect on liquidity ratios, where the results showed a noticeable improvement after the acquisition., there was a limited or indirect impact on activity ratios, while there was a negative impact on profitability ratios, which showed a noticeable and significant decline.
Keywords: استحواذ; توسع; أداء مالي; نسب مالية; أرامكو; سابك; Acquisition; expansion; financial performance; financial ratios; Aramco; SABIC